UPAYA MENINGKATKAN HASIL BELAJAR IPA MATERI ORGANISASI KEHIDUPAN TERHADAP PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) KELAS VII-3 SMP NEGERI 7 MEDAN TAHUN AJARAN 2018/2019 - Ukurta Br. Sinuraya (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2020)
The purpose of this study was to determine whether there was an increase in the learning outcomes of science learning in life organization materials through the Think Pair Share (TPS) cooperative learning model. Type of research (PTK). The method in this research uses quantitative data analysis. Based on the research results, as many as 30 students 94% got complete scores and as many as 2 students 4% got incomplete scores. It was found that students who got low scores were 0 students (0%), students who got moderate scores were 2 students (6%), students who got high scores were 11 students (33.3%) and students who got very high scores as many as 19 students (63.3%) with an average value of 87.33. Of the 32 students in cycle II, it was found that 94% were declared complete, while 2 students had not yet experienced completeness with an average score of 87.33.